Esquemas de criptografia de chave pública: elementos comuns e diferenciais - Ribeiro, Vinicius Gadis (2004)
Public key cryptography has been contributed some important functionality to computer systems security. Each pubic key scheme is based in some mathematics or computational problem, easy to solve in one way (an intended recipient) but hard to solve the inverse problem (an adversary). This paper presents a comparative study about computational problems, which is employed by public key cryptography schemes. It is reported a brief description of these problems, and a new public key scheme, called Rafaella, is presented. A comparative table containing the main features of the most commonly used public key methods is also presented.